Uncemented or cemented stems in first-time revision total hip replacement? An observational study of 867 patients including assessment of femoral bone defect size. (4th March 2021) - Tyson, Yosef; Hillman, Christer; Majenburg, Norbert; Sköldenberg, Olof; Rolfson, Ola; Kärrholm, Johan; Mohaddes, Maziar; Hailer, Nils P
Abstract : Background and purpose — Uncemented stems are gradually replacing cemented stems in hip revision surgery. We compared the risk of re-revision between uncemented and cemented revision stems and assessed whether the different fixation methods are used in similar femoral bone defects. Patients and methods — 867 patients operated on with uncemented or cemented stems in first-time hip revision surgery due to aseptic loosening performed 2006–2016 were identified in the Swedish Hip Arthroplasty Register. Preoperative femoral bone defect size was assessed on radiographs of all patients. Cox regression models were fitted to estimate the adjusted risk of re-revision during different postoperative time periods. Re-revision of any component for any reason, and stem re-revision, as well as risk of cause-specific re-revision was estimated. Results — Most patients in both fixation groups had Paprosky class IIIA femoral bone defects prior to surgery, but there were more severe bone defects in the cemented group. The adjusted risk of re-revision of any component for any reason was higher in patients with uncemented compared with those with cemented revision stems during the first 3 years after index surgery (hazard ratio [HR] 4, 95% confidence interval [CI] 2–9). From the 4th year onward, the risk of re-revision of any component for any reason was similar (HR 0.5, CI 0.2–1.4). Uncemented revision stems conferred a higher risk of dislocation compared with cemented stems (HR 5, CI 1.2–23) during the first 3 years. Interpretation — Although not predominantly used in more complex femoral defects, uncemented revision stem fixation confers a slightly higher risk of re-revision during the first years, but this risk is attenuated after longer follow-up.